RADON CONCENTRATION IN THE AREA OF WASTE ROCK DUMPS, BROD, CR-CASE STUDY - Thinova, L; Bican, R; Fronka, A; Johnova, K; Solc, J; Vosahlik, J (Radiation protection dosimetry, 2017)
There are ~7000 mining waste storage facilities including waste rock dumps in the Czech Republic. One of the radiation protection present subjects is a health impact estimation of the huge mass of material in waste rock dumps left after uranium mining. In this document are presented selected results of waste rock dump long-term monitoring in the area of shaft No. 15 (Pribram, CR) and its estimated health impact to the representative person in a village Brod. The external irradiation was estimated based on in situ gamma spectrometry measurement results and on a Monte Carlo model and it turned out to be negligible (tens μSv), while the internal irradiation (RAMARN, ALGADE Environmental and RAMONIS detection systems) is more significant. The estimated total annual effective dose for representative person is mainly caused by indoor radon inhalation. The maximum outdoor radon concentration in summer season was measured during night hours between 9 p.m. and 7 a.m. and could reach thousands Bq/m3. The average indoor concentration measured in randomly selected houses was 450 Bq/m3. The radon exhalation rate was 35-40 mBq m-2 s-1.
Keywords: Radon; dávka záření; monitorování radiace; radioaktivní látky znečišťující vzduch; Česká republika; Uranium; bydlení; Radiation Dosage; Czech Republic; Soil Pollutants, Radioactive; hornictví; lidé; Monte Carlo Method; Humans; radon; Housing; radioaktivní látky znečišťující půdu; Air Pollutants, Radioactive; metoda Monte Carlo; Environmental Exposure; Waste Disposal Facilities; skládková zařízení; znečištění vzduchu ve vnitřním prostředí; Air Pollution, Indoor; uran; vystavení vlivu životního prostředí; Mining; Radiation Monitoring